2020
DOI: 10.3390/en13143582
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inorganic Phase Change Material for a Semi-Transparent Photovoltaic (STPV) Module

Abstract: The semi-transparent photovoltaic (STPV) module is an emerging technology to harness the solar energy in the building. Nowadays, buildings are turning from energy consumers to energy producers due to the integration of the STPV module on the building envelopes and facades. In this research, the STPV module was integrated on the rooftop window of the experimental room at Kovilpatti (9°10′0″ N, 77°52′0″ E), Tamil Nadu, India. The performance of the STPV modules varies with respect to the geographical location, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…PV technology is largely applied into various areas. Such as solar still systems (Muthu Manokar et al, 2018aPounraj et al, 2018;Praveen Kumar et al, 2018;Kabeel et al, 2019;Balachandran et al, 2020;Sasikumar et al, 2020), self-powered room (Karthick et al, 2020), and etc.…”
Section: Introductionmentioning
confidence: 99%
“…PV technology is largely applied into various areas. Such as solar still systems (Muthu Manokar et al, 2018aPounraj et al, 2018;Praveen Kumar et al, 2018;Kabeel et al, 2019;Balachandran et al, 2020;Sasikumar et al, 2020), self-powered room (Karthick et al, 2020), and etc.…”
Section: Introductionmentioning
confidence: 99%
“…PV modules may be installed in either portrait (short edge down) or landscape (long edge down) configurations (Karthick et al, 2020). Previous field investigations conducted by the authors in this study have shown that modules in most industrial and commercial metal rooftop PV power stations with a lower tilt angle are installed in a portrait configuration, with few of them being installed in a landscape configuration at the central and eastern parts of China.…”
Section: Shapes Of Soiling Bandsmentioning
confidence: 97%
“…PV stations on the metal roofs of industrial and commercial buildings is one kind of building applied/attached PV (BAPV), which indicates the PV system is added/attached or applied to a building, while PV carport is one kind of building integrated PV (BIPV), which illustrates the concept of replacing the traditional building envelop, such as window, wall, roof by PV (Reddy et al, 2020). Both of them, especially BIPV, have been focused by researchers in recent times (Karthick et al, 2018(Karthick et al, , 2020Pichandi et al, 2020;Ramanan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Grid efficiency can be enhanced by controlling both suppliers and customers. Solar PV power could interfere with conventional power generation, making conventional generation uncomfortable or even unworkable [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%